1989
DOI: 10.1128/jcm.27.3.453-458.1989
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of influenza A virus infections by detection of specific immunoglobulins M, A, and G in serum

Abstract: The value of immunoglobulin M (IgM) detection in the early diagnosis of influenza A was examined in a prospective study during an outbreak of influenza A/Philippines/2/82 (H3N2) virus infection in February and March 1986. The IgM response was investigated in sera from 64 adults with influenzalike symptoms; we found a fourfold rise in titer or high titers (.80) of influenza A virus antibodies by the complement fixation test. The IgM response, analyzed by the hemadsorption immunosorbent technique, was compared w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…Therefore, if viral respiratory infection is the cause of BHR in asymptomatic subjects, it seems reasonable to believe that measurement of serum antibodies, as performed in the present study, can prove or refute the hypothesis that asymptomatic BHR is caused by recent viral respiratory infection. On the other hand, Vikerfors et al (35) found that serum antibodies against influ-enza A remain increased for at least 60 d, suggesting that the subjects in the present study with viral antibodies might have had respiratory illness within the last 60 d. These findings indicate that the subjects with antibodies might earlier have had BHR, but then, more than 6 weeks later, had returned to bronchial responsiveness within normal range, indicating that we overestimated recent or subclinical respiratory infection inducing BHR in the present study. Thus, only two subjects (12%) had BHR and viral antibodies against influenza B, whereas 15 subjects examined in the same period of 4 weeks, in which the epidemic was going on, had bronchial responsiveness within normal range.…”
Section: Bhr and Evidence Of Recent Vrimentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, if viral respiratory infection is the cause of BHR in asymptomatic subjects, it seems reasonable to believe that measurement of serum antibodies, as performed in the present study, can prove or refute the hypothesis that asymptomatic BHR is caused by recent viral respiratory infection. On the other hand, Vikerfors et al (35) found that serum antibodies against influ-enza A remain increased for at least 60 d, suggesting that the subjects in the present study with viral antibodies might have had respiratory illness within the last 60 d. These findings indicate that the subjects with antibodies might earlier have had BHR, but then, more than 6 weeks later, had returned to bronchial responsiveness within normal range, indicating that we overestimated recent or subclinical respiratory infection inducing BHR in the present study. Thus, only two subjects (12%) had BHR and viral antibodies against influenza B, whereas 15 subjects examined in the same period of 4 weeks, in which the epidemic was going on, had bronchial responsiveness within normal range.…”
Section: Bhr and Evidence Of Recent Vrimentioning
confidence: 99%
“…In any case, clinical data of respiratory illness are of uncertain value, since many of the respiratory viruses examined in the present study were accompanied by similar symptoms. Vikerfors et al (35) have found that the sensitivity ofthe ELISA to influenza A was 86%, and Meurman etal. (24) have found similar sensitivity ofthe ELISA-RSV (79%), suggesting that a substantial number of children and adolescents developed specific viral antibodies during a viral respiratory illness.…”
Section: Bhr and Evidence Of Recent Vrimentioning
confidence: 99%
“…Serology refers to the diagnostic identification of antibodies (Abs) in plasma serum and other body fluids [6]. The complement fixation test (CFT) is a classical serological method for the detection of Abs against infectious pathogens and has proven itself as a standard diagnostic method in many medical laboratories [6][7][8][9]. The key feature involved in CFT is the complement system, a component of the innate immune system that is characterized by serum proteins that react with antigen-antibody (Ag-Ab) complexes.…”
Section: Introductionmentioning
confidence: 99%
“…The ability of CFT in detecting IgG and IgM Abs has allowed its wide use in screening tests for acute primary infections and therapy successes [9]. CFT is also an important tool for monitoring the status of a person with a known autoimmune disease.…”
mentioning
confidence: 99%
“…The diagnostic value of specific total serum IgA antibodies as marker of virus infections is controversial [Halonen et al, 1979a,b;Nikoskelainen et al, 1979;Friedman and Kimmel, 1982;Sarov and Haikin, 1983;Sikuler et al, 1983;Strand and Hoddevik, 1984;Guglielmino et al, 1989;Vikerfors et al, 1989;Chau et al, 19931. In contrast, different reports have shown the usefulness of virus-specific polymeric IgA as indicator of acute or recent infection [Negro Ponzi et al, 1985;Hashido et al, 1989;Kawano and Minamishima, 19921. Against this background, the presence of heterotypic enteroviral total and polymeric IgA antibodies in serum from patients with acute enterovirus infections were examined and compared with sera from patients with other infections. The presence of heterotypic enteroviral total IgA antibodies in serum samples from blood donors that were collected in different seasons was also investigated and compared.…”
Section: Introductionmentioning
confidence: 99%